Therapeutic potential of isochlorogenic acid A from Taraxacum officinale in improving immune response and enhancing the efficacy of PD-1/PD-L1 blockade in triple-negative breast cancer - Wang, Tangyi; Sun, Jingwei; Wang, Li; Lin, Yuxin; Wu, Zhijing; Jia, Qiangqiang; Zhang, Shoude; An, Juan; Ma, Xueman; Wu, Qiong; Su, Zhanhai; Wang, Haiyan (Frontiers in Immunology, 2025)
IntroductionTaraxacum officinale, a traditional medicinal herb, has garnered significant attention for its potential role in the prevention and treatment of breast cancer. Although clinical recognition of its efficacy has gradually increased, research has shown that Taraxacum officinale contains a variety of chemical components, including triterpenes, carbohydrates, flavonoids, phenolic acids, sesquiterpenes, coumarins, fatty acids, and organic acids. However, the pharmacological mechanisms underlying Taraxacum officinale’s effects and the identification of its key bioactive components warrant further investigation.MethodsFlow cytometry was utilized to investigate the effects of Taraxacum officinale extract (TOE) in combination with PD-1/PD-L1 inhibitor 2 on the immune microenvironment of triple-negative breast cancer (TNBC). Active compounds and their potential targets were identified through an integrative approach involving GeneCards, OMIM, and DisGeNET databases, as well as UPLC-Q-Orbitrap MS analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted, followed by molecular docking to explore compound-target interactions. The anti-proliferative effects of isochlorogenic acid A (ICGA-A) and chicoric acid (CRA) on MDA-MB-231 and 4T1 cells were evaluated using the CCK-8 assay. In vivo validation was performed using a 4T1 murine model and flow cytometry.ResultsTOE and its active constituents, ICGA-A and CRA, demonstrate potential in augmenting PD-1 blockade therapy for TNBC. This study investigated the combination of ICGA-A and PD-1/PD-L1 inhibitor 2, which significantly enhanced the infiltration of macrophages and CD8+ T cells into tumors in murine models, while concurrently reducing the population of exhausted T cells. Furthermore, CRA notably increased the frequency of CD8+ T cells. Both ICGA-A and CRA therapies were also found to suppress tumor proliferation by inhibiting the FAK/PI3K/AKT/mTOR signaling pathway. These findings highlight the potential of ICGA-A and CRA as effective adjuvants to improve the therapeutic efficacy of PD-1 inhibitor-based immunotherapy in TNBC.DiscussionICGA-A and CRA, bioactive compounds from Taraxacum officinale, exhibit significant antitumor activity in TNBC by targeting the FAK/PI3K/AKT/mTOR pathway, a critical regulator of cancer progression. Their ability to modulate the tumor immune microenvironment highlights their potential as immune modulators that enhance the efficacy of immunotherapy. These findings suggest that ICGA-A and CRA could serve as promising adjuncts in TNBC treatment, offering a novel strategy to overcome challenges such as therapeutic resistance and limited treatment options. Further investigation is warranted to explore their synergistic effects with immunotherapies in improving TNBC outcomes.